2018
DOI: 10.14689/ejer.2018.74.4
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Profile of Early Childhood Education Preservice Teachers

Abstract: Purpose: Teachers are key determiners of quality education, and regarding young children in particular, the quality of teachers can have a remarkable influence on the quality of education. However, research on the socioeconomic profile of preservice teachers at university remains rare in Turkey, especially eastern Turkey, where living conditions are below of the national average. In our study, the socioeconomic profile of 2,115 early childhood teacher candidates in faculties of education at state universities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this context, meeting the training needs of pre-service teachers for these skills is seen as a necessity in terms of their success and that of their students in their professional lives. Teachers, who are the main determinants of education, have a significant impact on a quality education (Unal & Kurt, 2018). Especially preschool teachers and teacher candidates should know children well and have the ability to gather information about children.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, meeting the training needs of pre-service teachers for these skills is seen as a necessity in terms of their success and that of their students in their professional lives. Teachers, who are the main determinants of education, have a significant impact on a quality education (Unal & Kurt, 2018). Especially preschool teachers and teacher candidates should know children well and have the ability to gather information about children.…”
Section: Discussionmentioning
confidence: 99%
“…23, e21 3 emotional competencies (Fernández et al, 2019) and/or by theoretical preferences in explaining toddler behavior (Mischo et al, 2012). Other studies have identified educators' professional competencies based on the country's educational policies (Oberhuemer, 2015), socio-demographic variables (Unal & Kurt, 2018), characteristics relating to their professional identity (Doğan & Erdiller, 2016) and/or variables of a psychological nature such as the degree of emotional support provided to children (Treviño et al, 2013), attitudes toward early learning (Jeon et al, 2015), and personality traits (Tatalović et al, 2018).…”
Section: Evidence-based Characterizations Of Early Childhood Educatorsmentioning
confidence: 99%